EVALUASI KEBIJAKAN PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 66 TAHUN 2015 MENGENAI MUSEUM PADA MUSEUM MPU TANTULAR - Endik Hidayat; Jennifer Jennifer; Dewi Rahmawati; Nesy Hari Pratiwi (Journal Publicuho, 2021)
The Mpu Tantular Museum is one of the cultural heritages in the city of Sidoarjo which provides various artifacts and relics of the kingdom and the ancestors of the Indonesian nation, especially in the city of Surabaya and Sidoarjo. The implementation of Government Regulation No.66 of 2015 concerning museums is a rule that must be obeyed by the museum managers. But today there are still many museums in Indonesia that are not maintained and even neglected, this shows that there is an error in the implementation of these regulations. In this study using a qualitative descriptive method with a literature study approach. Researchers used observation techniques, interviews in making this study, the results of the study showed that there were several causes and obstacles that occurred in the running of the Mpu Tantular museum activities, namely the influence of globalization and also the influence of the Covid-19 pandemic which made no visitors come to the museum. thus reducing the income budget that is commonly used in managing, maintaining and providing salaries for employees.